THE USE OF OXIDATIVE STRESS BIOMARKERS IN PREDICTING ONCOGENIC TRANSFORMATION OF LEUKOPLAKIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Rasulova Nargiza Azamatovna; Khabibova Nazira Nasulloyevna (Modern American Journals, 2025)
The study investigates the prognostic significance of oxidative stress biomarkers in identifying oncogenic transformation potential in oral leukoplakia among patients with type 2 diabetes mellitus. The analysis included quantification of nitric oxide, 3-nitrotyrosine, malondialdehyde, and carbonylated proteins in blood serum, with concurrent assessment of thiol status and ceruloplasmin as antioxidant parameters. Biomarker dynamics were correlated with glycemic control stages. In decompensated patients, a critical elevation in oxidative markers was observed, notably a 300-fold increase in 3-nitrotyrosine, accompanied by a marked suppression of thiol groups and ceruloplasmin levels. The findings reflect sustained redox imbalance and biochemical destabilization of epithelial structures. The data indicate a direct association between intensified oxidative stress and epithelial transformation risk in leukoplakia under diabetic conditions.